HOW GOOD IS THE INTERNAL AUDIT FUNCTION OF INDONESIAN SOES FOR BPK RI? - Nanang Nawari; Dian Kusuma Wardhani (Universitas Airlangga, 2022)
The increase in BPK RI's audit findings on the SPI of SOEs seems to indicate a decline in the quality of the SPI of the state-owned company. Dzikrullah et al. (2020) show that the internal audit's characteristics or internal audit function, namely the expertise and certification of internal auditors, influence the audit results. This study seeks to explore the findings of Dzikrullah et al. (2020) by analyzing the characteristics of the internal audit function into a sample of the state-owned enterprise. The aim is to obtain empirical evidence of the negative influence of the internal audit function on the results of the BPK RI audit of the SOE's SPI. Agency theory and upper echelon are used to explain the effect of SOEs' internal audit characteristics on the audit results of BPK RI. The research sample consisted of 70 observational data of non-financial SOE during 2014 – 2019. The observation data were processed using stats version 14 with multiple linear regression analysis techniques. The research findings show that expertise does not affect the results of the BPK RI audit. However, the certification has a negative effect on audit results.